2020
DOI: 10.1097/j.pain.0000000000002070
|View full text |Cite
|
Sign up to set email alerts
|

Balloon compression vs radiofrequency for primary trigeminal neuralgia: a randomized, controlled trial

Abstract: Surgical procedures are necessary in up to 50% of trigeminal neuralgia patients. Although radiofrequency (RF) is more widely used, it is associated with high intraprocedural costs and long technical learning time. Other simpler procedures such as balloon compression (BC) require a lower training period and have significant lower costs. We evaluated the effects of BC and RF in pain control in primary trigeminal neuralgia in a randomized, double-blinded, head-to-head trial. Individuals were randomly allocated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…Except PBC, other microinvasive approaches, such as gamma knife radiotherapy, glycerol rhizotomy, and radiofrequency thermocoagulation, were also reported to be useful in treatment of ITN [1,[6][7][8][9]. A recently published meta-analysis concerning TN showed that glycerol rhizotomy showed similar rate of immediate pain relief and pain recurrence with PBC but showed lower incidences of numbness and diplopia, while the incidences of other complications were similar in both groups [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Except PBC, other microinvasive approaches, such as gamma knife radiotherapy, glycerol rhizotomy, and radiofrequency thermocoagulation, were also reported to be useful in treatment of ITN [1,[6][7][8][9]. A recently published meta-analysis concerning TN showed that glycerol rhizotomy showed similar rate of immediate pain relief and pain recurrence with PBC but showed lower incidences of numbness and diplopia, while the incidences of other complications were similar in both groups [9].…”
Section: Discussionmentioning
confidence: 99%
“…Different from other subgroups where neurovascular compression or underlying diseases can easily be identified, ITN does not show significant abnormalities in electrophysiological tests or MRI scans, which makes etiological targeted surgeries impossible [5]. Other surgeries, such as percutaneous balloon compression (PBC), gamma knife radiotherapy, glycerol rhizotomy, and radiofrequency thermocoagulation, have repeatedly been reported to be useful for pain control in TN for which pharmacological treatments have failed [1,[6][7][8][9]. Among these surgical options, PBC is a commonly used microinvasive technique and shows potential in the control of TN [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The precise acquisition of MC morphological data through the radiomics method is beneficial for the preparation of PBC for PTN. PBC requires the puncture of the MC and filling up of the balloon to compress the semilunar ganglion nerve 36 . The accurate evaluation of the MC volume before PBC can not only provide reference for the balloon filling volume, but also prepare appropriate balloon volume for some special MC volumes (the maximum volume of MC in this study was 1589.90 mm3).…”
Section: Discussionmentioning
confidence: 99%